2013
DOI: 10.1037/a0032014
|View full text |Cite
|
Sign up to set email alerts
|

Associations between smoking and psychiatric comorbidity in U.S. Iraq- and Afghanistan-era veterans.

Abstract: Introduction The risk of smoking increases with specific psychiatric diagnoses (e.g. posttraumatic stress disorder [PTSD]); but the risk has also been shown to increase as a function of the number of psychiatric illnesses with which a person is diagnosed. The current study examined this association and other correlates of smoking-psychiatric comorbidity in a sample of U.S. Iraq/Afghanistan era Veterans who have served since September 11, 2001. Methods The sample consisted of 1691 Veterans (mean age = 37.5 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…In the current review, only 1 out of the 33 studies (McClernon, Calhoun, Hertzberg, Dedert, & Beckham, 2013) used a structured clinical interview to assess PTSD. Structured clinical interviews are considered the gold standard assessment methodology for psychiatric diagnosis given their increased reliability and validity (Rogers, 2001;Segal & Coolidge, 2003).…”
Section: Limitations Of Current Research On Prevalence Of Ptsd Among mentioning
confidence: 99%
“…In the current review, only 1 out of the 33 studies (McClernon, Calhoun, Hertzberg, Dedert, & Beckham, 2013) used a structured clinical interview to assess PTSD. Structured clinical interviews are considered the gold standard assessment methodology for psychiatric diagnosis given their increased reliability and validity (Rogers, 2001;Segal & Coolidge, 2003).…”
Section: Limitations Of Current Research On Prevalence Of Ptsd Among mentioning
confidence: 99%
“…Twenty-nine studies reported the prevalence of prior or current PTSD among current or lifetime users of tobacco products (Alexander, Ali, McDevitt-Murphy, et al, 2017;Baggett, Campbell, Chang, Magid, & Rigotti, 2016;Farris, 2015;Farris, 2016;Farris, Vujanovic, Hogan, Schmidt, & Zvolensky, 2014;Farris, Zvolensky, Beckham, Vujanovic, & Schmidt, 2014;Flanagan, Hakes, McClure, et al, 2016;Garey, Cheema, Otal, et al, 2016;Greenberg, Ameringer, Trujillo, et al, 2012;Hermes et al, 2012;Hruska, Bernier, Kenner, et al, 2014;Jessup, Dibble, & Cooper, 2012;Lawrence et al, 2009;Lombardero et al, 2014;Lopez, Konrath, & Seng, 2011;Lopez & Seng, 2014;Mahaffey, Gonzalez, Farris, et al, 2016;Mathew et al, 2015;McClernon, Calhoun, Hertzberg, et al, 2013;Roberts et al, 2015;Sawchuk et al, 2012;Sawchuk, Roy-Byrne, Noonan, et al, 2016;Van der Velden et al, 2007;Weber, Boggero, Carlson, et al, 2016;Young-Wolff et al, 2014;Zvolensky, 2014;Zvolensky, Farris, Schmidt, & Smits, 2014;Zvolensky, Vujanovic, Miller, et al, 2007). Of these studies, twenty-five explored rates of PTSD among cigarette smokers, two among smokeless tobacco users (Hermes et al, 2012;Sawchuk et al, 2012), and the other two among users of other combustible tobacco products (Roberts et al, 2015;Van der Velden et al, 2007).…”
Section: Prevalence Of Ptsd Among Individuals Using Tobacco Products mentioning
confidence: 99%
“…Rates of smoking are generally higher among individuals with multiple psychiatric disorders 6 , and persons who are homeless are more likely to have multiple psychiatric disorders 7 . Homeless veterans are four times as likely to have a diagnosis of nicotine dependence compared to veterans who are not homeless 8 , independent of their increased risk for other substance-use disorders.…”
Section: Introductionmentioning
confidence: 99%